The Effect of Islamic Leadership, Organizational Culture, and Self-Efficacy on Lecturer Performance Mediated Organizational Citizenship Behavior (OCB) at Islamic Religious Colleges in West Kalimantan Indonesia - Juliansyah, Juliansyah; Ridwan, Muhtadi; Wahidmurni (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – Building performance is one of the fundamental goals of every tertiary institution. The lecturer profession is increasingly competitive, and the difficulty in raising the competence of lecturers who are partly in the Islamic boarding school environment determines whether Islamic tertiary institutions survive. This study examines the influence of Islamic Leadership, organizational culture, and self-efficacy on lecturer performance mediated by Organizational Citizenship Behavior (OCB). Design/methods/approach – This research was conducted on 202 lecturers at an Islamic religious university in West Kalimantan, Indonesia. This type of correlational research with survey techniques using the SmartPLS 3.3.7 application. Findings – From the results of the study, it was found that there was a significant influence of Islamic Leadership on OCB; there is a significant influence of organizational culture on OCB; there is a significant effect of self-efficacy on OCB; there is no significant effect of Islamic Leadership on performance; there is no significant effect of organizational culture on performance; there is a significant effect of self-efficacy on performance; there is a significant effect of OCB on performance; and there is a significant effect of Islamic Leadership, organizational culture, and self-efficacy on OCB-mediated performance. This study contributes to a new paradigm of lecturer performance: OCB as the dominant variable construct that mediates civic virtue and altruism values. Research implications/limitations – This study emphasizes that improving lecturer performance is not enough with spiritual leadership, organizational culture, and self-efficacy but assisted by organizational citizenship behavior (OCB). Practical implications – This study shows a relationship between Islamic leadership, organizational culture, self-efficacy, and OCB variables on lecturer performance and gives the importance of strengthening OCB to improve lecturer performance.